Phylogenetic Analysis and Mutation of Sars-Cov-2 in Bats in Karst Malang City, Indonesia - Keman, Soedjajadi; Moch Irfan Hadi; Dedy Suprayogi; Yudied Agung Mirasa (Universitas Airlangga, 2024)
Introduction: A group of people in China were hospitalized with an initial diagnosis of pneumonia of unknown cause. The patients were linked to a wholesale wet seafood and animal market in Wuhan, Hubei Province, China. The disease has spread to other provinces in China, Thailand, Japan, and South Korea in less than a month. SARS-CoV-2 was found to originate from bats. Therefore, this research aims to analyze SARS-CoV-2 mutation in bats in Malang Karst, Indonesia. Methods: Other bat body parts used as research samples include the brain, liver, kidneys, intestines, pancreas, fetus, blood, lungs, and ectoparasites. The samples were taken separately and placed in a container containing 10% PBF. For further analysis, we used RNA Extraction, Real-Time PCR, Sequencing, and CoV Gisaid mutation analysis software to analyze the sequencing data. Then, EMBL software will be used to analyze the phylogenetically. Results and Discussion: There was 1 sample that showed a positive result for Covid-19, namely the intestine of the Cynoptera brachyotis species. There were differences between SARS-CoV-2 in bats in Malang Karst in Indonesia compared to SARS-CoV from 2000 to 2019. The spike protein's receptor binding domain (RBD) is the most variable part of the coronavirus genome. Conclusion: From the research results, one positive sample was obtained using Real-Time PCR, and based on mutation analysis, mutations were found in SARS-CoV-2 against the SARS-CoV virus from 2000-2019. Further research is needed, especially regarding SARS-CoV-2 as a vaccine.